URGENSI HUKUM BISNIS INDONESIA YANG BERBASIS NILAI-NILAI SOSIAL BUDAYA - Ida Bagus Radendra Suastama (STIMI Handayani Denpasar, 2021)
This paper objective is to examine the ideas related to the importance of designing and enforcing legal principles and rules that based on the values that live and applied in society, especially in the field of business law. Business Law includes, among others, company law, commercial law, investment law, civil law, intellectual property law, capital market law, banking law, consumer protection law, anti-monopoly law, and others. Some of the contents of the current provisions of business law in Indonesia are based on values that are not native to Indonesia. With the recent trend of free trade which tends to be based on capitalistic and neo-liberalistic thinking, the tendency to adopt uniform values from global relations also seems to be increasing. This paper aims to find out the importance of local / regional socio-cultural values originating from Indonesia as a source of content and regulation of business law in Indonesia. The approach method in this research is a normative legal research method with a qualitative research approach. This research comes to the conclusion that based on literature research on legal ideas, it is necessary to have an inventory of the values of original Indonesian legal principles related to the design and application of legal principles and principles that take into account the living and applied values in society, and that the original local / regional sociocultural values of Indonesia should be optimized as the source of the content and regulation of business law in Indonesia.